Factors affecting the organizational performance of manufacturing firms - Ahmad Adnan Al-Tit (International Journal of Engineering Business Management, 2017)
Numerous studies have been conducted to explore the individual effects of organizational culture (OC) and supply chain management (SCM) practices on organizational performance (OP) in different settings. The aim of this study is to investigate the impact of OC and SCM on OP. The sample of the study consisted of 93 manufacturing firms in Jordan. Data were collected from employees and managers from different divisions using a reliable and valid measurement instrument. The findings confirm that both OC and SCM practices significantly predict OP. The current study is significant in reliably testing the relationship between SCM practices and OP; however, it is necessary to consider cultural assumptions, values and beliefs as the impact of OC on OP is greater than the impact of SCM practices. Based on the results, future studies should consider the moderating and mediating role of OC on the relationship between SCM practices and OP.